2019
DOI: 10.1111/jace.16874
|View full text |Cite
|
Sign up to set email alerts
|

Engineering cation vacancies to improve the luminescence properties of Ca14Al10Zn6O35: Mn4+ phosphors for LED plant lamp

Abstract: In the recent years, Mn4+‐doped phosphors for indoor plant cultivation have received extensive concern owing to the far‐red emission that can match well with the absorption spectra of plant pigments. Whereas, many Mn4+‐doped phosphors still face some challenges such as poor light efficiency and low thermal stability. It is an effective way to resolve these problems via cation vacancies engineering. Herein, the Ca14−xAl10Zn6−yO35: Mn4+ phosphors are successfully synthesized by combustion method. The luminescenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 46 publications
0
20
0
Order By: Relevance
“…Note that the activation energy DE 1 is equal to that obtained from the temperature-dependent emission intensity by eqn (14), while the smaller activation energy DE 2 is equal to hv 4 . In comparison, eqn (18) shows the best fit to the fluorescence lifetimes, and the fitting yields t 0 = 6.39 ms, tn R = 7.09 Â 10 À7 ms, hv = 0.0365 eV (B295 cm À1 ; hv 6 o hv o hv 4 ) and DE = 0.79 eV. The values of both DE 2 in eqn (15) and hv in eqn (18) are of the same order of magnitude as the lattice vibration energy, and thus can be regarded as a reflection of the contribution from vibration.…”
Section: Temperature Dependence Of Photoluminescence Propertiesmentioning
confidence: 94%
See 4 more Smart Citations
“…Note that the activation energy DE 1 is equal to that obtained from the temperature-dependent emission intensity by eqn (14), while the smaller activation energy DE 2 is equal to hv 4 . In comparison, eqn (18) shows the best fit to the fluorescence lifetimes, and the fitting yields t 0 = 6.39 ms, tn R = 7.09 Â 10 À7 ms, hv = 0.0365 eV (B295 cm À1 ; hv 6 o hv o hv 4 ) and DE = 0.79 eV. The values of both DE 2 in eqn (15) and hv in eqn (18) are of the same order of magnitude as the lattice vibration energy, and thus can be regarded as a reflection of the contribution from vibration.…”
Section: Temperature Dependence Of Photoluminescence Propertiesmentioning
confidence: 94%
“…In comparison, eqn (18) shows the best fit to the fluorescence lifetimes, and the fitting yields t 0 = 6.39 ms, tn R = 7.09 Â 10 À7 ms, hv = 0.0365 eV (B295 cm À1 ; hv 6 o hv o hv 4 ) and DE = 0.79 eV. The values of both DE 2 in eqn (15) and hv in eqn (18) are of the same order of magnitude as the lattice vibration energy, and thus can be regarded as a reflection of the contribution from vibration. It is found that the two curves fitted by eqn ( 17) and ( 18) are perfectly coincident below 420 K, which indicates the absolute dominance of the radiation transition.…”
Section: Temperature Dependence Of Photoluminescence Propertiesmentioning
confidence: 94%
See 3 more Smart Citations